Goodman & Gilman's the pharmacological basis of therapeutics - Brunton, Laurence L; Knollmann, Björn C. (McGraw Hill, 2023)
"The first edition of this book appeared in 1941, the product of a collaboration between two friends and professors at Yale, Louis Goodman and Alfred Gilman. Their purpose, stated in the preface to that edition, was to correlate pharmacology with related medical sciences, to reinterpret the actions and uses of drugs in light of advances in medicine and the basic biomedical sciences, to emphasize the applications of pharmacodynamics to therapeutics, and to create a book that would be useful to students of pharmacology and to physicians. We continue to follow these principles"--